Good Shepherd Sunday: A Morphological Study of Derivational Affixes in Pope Leo XIV’S Speech - Salwa Khuzaimatu; Otong Setiawan Djauhari (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to analyze the derivational affixes found in the Regina Caeli speech delivered by Pope Leo XIV. The main focus of the research is to identify the types of derivational affixes and determine their frequency, including both prefixes and suffixes. The research applies a mixed methods approach, combining both quantitative and qualitative descriptive methods. The quantitative aspect involves identifying and counting the types and frequency of derivational affixes found in Pope Leo XIV’s speech at Regina Caeli. The qualitative aspect focuses on analyzing the contextual meaning and function of those affixes within the speech. Data collection techniques include textual analysis.. Based on the analysis, a total of 13 types of derivational affixes were identified, consisting of one prefix and 12 suffixes. Furthermore, derivational affixes in this study are classified into four types: noun, verb, adjective, and adverb derivation. This study is expected to encourage English learners to understand and apply derivational affixes effectively, as doing so can significantly enrich vocabulary and enhance linguistic competence by recognizing root words and how new forms are created. This classification helps English learners expand vocabulary and understand how word forms are systematically built, thus enhancing their language skills.